2021
DOI: 10.1097/med.0000000000000658
|View full text |Cite
|
Sign up to set email alerts
|

Renal function in patients following a low carbohydrate diet for type 2 diabetes: a review of the literature and analysis of routine clinical data from a primary care service over 7 years

Abstract: Purpose of review People with T2 Diabetes (T2D) who follow a low carbohydrate diet (LCD) may increase their dietary protein intake. Dietary protein can modulate renal function so there is debate about its role in renal disease. There is concern that higher protein intakes may promote renal damage, and that LCDs themselves may impact on cardiovascular risk. We review the evidence around LCDs, renal and cardiovascular risk factors and compare to results obtained in a real-world, primary care setting.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 51 publications
0
15
0
Order By: Relevance
“…In patients with DCKD stages 3 to 5, each 10 mm Hg increase in mean SBP has been associated with a 15% increase in the hazard ratio for the development of both micro- and macroalbuminuria and impaired kidney function [ 28 ]. In a recent study, the mean improvement in SBP of 11,7 mm Hg amongst a cohort of 143 patients with normal function or only mild DCKD significantly improved the serum creatinine over an average of 30 months, suggesting that the improvement could be due, at least in part, to the reduction in BP [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…In patients with DCKD stages 3 to 5, each 10 mm Hg increase in mean SBP has been associated with a 15% increase in the hazard ratio for the development of both micro- and macroalbuminuria and impaired kidney function [ 28 ]. In a recent study, the mean improvement in SBP of 11,7 mm Hg amongst a cohort of 143 patients with normal function or only mild DCKD significantly improved the serum creatinine over an average of 30 months, suggesting that the improvement could be due, at least in part, to the reduction in BP [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…In a recent practice-based cohort study in the UK including 143 type 2 diabetes patients with normal renal function or mild CKD adhering to a low carb diet it was found that over an average of 30 months serum creatinine improved significantly with a mean of 4.7 (14.9) μmol/L. 18 The effects of Reverse Diabetes2 Now have been investigated in the setting of a pragmatic trial, which inherently has advantages and disadvantages. Data quality and collection can be limiting, since researchers are dependent on the data collection through regular care.…”
Section: Discussionmentioning
confidence: 99%
“…In the general population, it was demonstrated that both high and low percentages of carbohydrate diets were associated with increased mortality, with the lowest risk reported at 50-55% energy from carbohydrate [100]. Moreover, recent studies support that low carbohydrate diets (LCDs) may improve many renal and cardiovascular risk factors in patients with T2DM [101].…”
Section: Carbohydratesmentioning
confidence: 99%
“…To date, there has been much controversy related to macromineral intake for both CHD and T2DM patients. Many studies have demonstrated that water calcium has a protective role against cardiovascular events [98][99][100][101][102][103][104][105], while others found no relationship between calcium and CVD [106] or T2DM [107]. Other macrominerals, such as phosphorus, potassium, and magnesium, are involved in different components of the metabolic syndrome (e.g., insulin secretion) [108].…”
Section: Macromineralsmentioning
confidence: 99%